1984
DOI: 10.1055/s-2008-1044298
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Methods of Prophylaxis Against CSF Shunt Infection

Abstract: In a series of 68 operations for insertion or revision of cerebrospinal fluid shunts the incidence of infection was reduced from 20% in controls to 4.2% when systemic and intrathecal or intra-shunt gentamicin prophylaxis was employed. The only infection occurring in the latter group was due to an organism resistant to gentamicin. No reduction in infection rate was noted when povidone iodine was instilled into the wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
(13 reference statements)
0
18
0
Order By: Relevance
“…34 However, because most studies are performed retrospectively and can be underpowered at single centers, they frequently arrive at opposing conclusions. Areas of ongoing controversy in the prevention of CSF shunt infection include the use of prophylactic IT antibiotics; 30,39,44,45 type of shunt; 31,46 antibiotic impregnated shunt tubing; 4750 distal shunt location; 29,31,32,35,36,51 use of neuroendoscope; 12,34 duration of case; 34,36,40,51 case priority; 30,32,34,40 and people in the operating room. 34,39,40 In this study, none of the surgeon factors or medical and surgical decisions contributed substantially to infection risk beyond CSF shunt revision itself.…”
Section: Discussionmentioning
confidence: 99%
“…34 However, because most studies are performed retrospectively and can be underpowered at single centers, they frequently arrive at opposing conclusions. Areas of ongoing controversy in the prevention of CSF shunt infection include the use of prophylactic IT antibiotics; 30,39,44,45 type of shunt; 31,46 antibiotic impregnated shunt tubing; 4750 distal shunt location; 29,31,32,35,36,51 use of neuroendoscope; 12,34 duration of case; 34,36,40,51 case priority; 30,32,34,40 and people in the operating room. 34,39,40 In this study, none of the surgeon factors or medical and surgical decisions contributed substantially to infection risk beyond CSF shunt revision itself.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Because CNS infections after shunting procedures are responsible for substantial mortality and morbidity, especially in children, the possible role of prophylactic antimicrobials in such procedures has been studied in numerous small, well-conducted, randomized controlled trials. [564][565][566][567][568][569][570][571] Meticulous surgical and aseptic techniques and short procedure times were determined to be important factors in lowering infection rates after shunt placement. Although the number of patients studied in each trial was small, two meta-analyses of these data demonstrated that antimicrobial prophylaxis use in CSF-shunting procedures reduced the risk of infection by approximately 50%.…”
Section: Neurosurgery Proceduresmentioning
confidence: 99%
“…This investigation underlines the problem with too low a number of patients [41] which seems to be a general feature in most negative studies of prophylactic antibiotics [3,26,55].…”
Section: Prophylaxis Against Infectionsmentioning
confidence: 98%